Pinpointing drivers of widespread colonization of Legionella pneumophila in a green building: Roles of water softener system, expansion tank, and reduced occupancy - Joshi, Sayalee; Richard, Rain; Levya, Carlos; Harrison, Joanna Ciol; Saetta, Daniella; Sharma, Naushita; Crane, Lucas; Mushro, Noelle; Dieter, Lucien; Morgan, Grace V.; Heida, Ashley; Welco, Bennett; et al. (Frontiers in Water, 2023)
Legionella pneumophila is an opportunistic pathogen that is a key contributor to drinking water-associated disease outbreaks in the United States. Prolonged water stagnation periods in building plumbing systems due to low occupancy, especially during building shutdowns, breaks, and holidays, can lead to water quality deterioration and (re)colonization of buildings with L. pneumophila. Water monitoring in buildings typically relies upon on grab samples with small datasets. In this study, a larger dataset was created by sampling a Leadership in Energy and Environmental Design (LEED)-certified data-rich commercial building for L. pneumophila and physical-chemical water quality during the COVID-19 pandemic after reduced building occupancy. A proxy for human occupancy rates using WIFI logins was recorded throughout the study period. L. pneumophila was observed in grab samples taken throughout the building, where concentrations generally increased with greater distances from the building point of entry to locations throughout the building. Factors conducive to microbial growth were identified in the building including fluctuations in water temperatures, lack of chlorine residual, a low water heater setpoint, colonized water-saving fixtures, prolonged stagnation throughout the building and especially in an expansion tank designed to reduce pressure issues during demand fluctuations, and the presence of oversized softener tanks with ion exchange resin that contributed to chlorine residual removal as well as colonization of the resin with L. pneumophila. Flushing and thermal disinfection alone did not resolve the problem, and replacement of the expansion tank ultimately resolved the L. pneumophila issue. As ad-hoc approaches are logistically- and time-intensive, more proactive approaches are needed for informing preventative and corrective actions for reducing the risk of exposure to opportunistic pathogens in the building plumbing.